A convenient method for the preparation of radioiodinated meta‐iodobenzylguanidine at a no‐carrier‐added level. (22nd September 2015) - Wang, Gang; Chen, Zhiming; Wu, Erming; Wang, Yang; Huang, Heyun
Abstract : Radioiodinated meta‐iodobenzylguanidine (MIBG) in high effective specific activity was prepared using 3‐tributylstannylbenzylguanidine as the precursor. The labeling was carried out in aqueous solution with the insoluble and lyophilized precursor suspended in the solvent. Simply by filtration, the starting material and by‐products were readily separated from the labeled solution. Less than 1.15 ppb tin has remained in the filtrate as determined by the atom fluorescence spectrometry. By this approach, high specific activity (3.4 GBq/µmol) [ 131 I]MIBG was obtained in 72.3 ± 3% ( n  = 3) radiochemical yield and 97.3 ± 2% ( n  = 3) radiochemical purity. The whole preparation could be finished in less than 10 min. According to this method, a kit for the preparation of 123 I‐MIBG and 131 I‐MIBG is currently being developed. Abstract : Radioiodinated meta ‐iodobenzylguanidine in high specific activity (3.4 GBq/µmol) was prepared in pure water system using 3‐tributylstannylbenzylguanidine as the precursor with 72.3±3% ( n  = 3) radiochemical yield and 97.3±2% ( n  = 3) radiochemical purity. The purification only involved filtration, and the whole preparation could be finished in less than 10 min.